Local calcium carbonate powder: its properties and application as fillers - Junin, Radzuan; Mustapha, Saari (Faculty of Chemical & Natural Resources Engineering, UTM Skudai, 1988)
Calcium carbonate powder used as filler is produced from limestone. It is extremely difficult to define the limits of this mineral category. Its definition depends more on its uses than on its physical or chemical properties. Calcium carbonate filler comes in two forms: ground and light. Ground calcium carbonate is a low quality product and is much cheaper than light calcium carbonate. It has been widely used in several industries. For several purposes. Calcium carbonate filler must have high brightness and vary in size from nominal 325 mesh to submicron material. For plastics and pain industry, they must have low oil absorption and ease of dispersion. Quantitative analysis of the market is difficult to compile due to lack of statistics in the field. However, the polymer and paint industry are the largest consumer of white carbonate filler. Calcium carbonate is essentially a fairly cheap product, despite the fact that sophisticated techniques are used in its production.